Faunistical and ecological analysis of digger wasps (Hymenoptera: Sphecidae, Crabronidae) in Uzbekistan - Medetov, Makhsetbay Zh.; Embergenov, Muratbay A.; Kholmatov, Bakhtiyor R.; Elmurodova, Muhayyo V.; Rakhimov, Matnazar Sh.; Tajibaeva, Juldizkhan D. (Acta Biologica Sibirica, 2024)
This article presents the results of scientific research conducted in 2021–2023 on the study of digger wasps belonging to the Sphecidae, Crabronidae family in different regions of Uzbekistan, as well as the results of the study of literature sources. Total 484 species of which 69 species belonging to Sphecidae family, 415 species to Crabronidae family, 21 tribes and 74 genera were recorded in our republic. In terms of subspecies, Crabroninae equals to 24.8%, Bembicinae 18.2%, Philanthinae 17.8 %, Eremiaspheciinae 15.7 %, Ammophilinae 7.2 %, Pemphredoninae 6.6 %, Sphecinae 5.2 %, Astatinae 2.1%, Sceliphrinae 1.8 % and Dinetinae 0.6 %. 125 species were identified in the North-Western region of Uzbekistan, 253 species in the North-Eastern region, 66 species in the Eastern region, 261 species in the Central region, and 101 species in the Southern region. The digger wasp species in the North-Western and Central regions of Uzbekistan have the closest similarity of 30%, and the Eastern and Southern regions have the furthest similarity. 48% of digger wasps are native to desert, 35% to mountain and lowlands and least agrocenosis landscapes.